A Branch and Bound Reduced Algorithm for Quadratic Programming Problems with Quadratic Constraints. (11th November 2013) - Gao, Yuelin; Li, Feifei; Jin, Siqiao
Abstract : We propose a branch and bound reduced algorithm for quadratic programming problems with quadratic constraints. In this algorithm, we determine the lower bound of the optimal value of original problem by constructing a linear relaxation programming problem. At the same time, in order to improve the degree of approximation and the convergence rate of acceleration, a rectangular reduction strategy is used in the algorithm. Numerical experiments show that the proposed algorithm is feasible and effective and can solve small- and medium-sized problems.